IDENTIFIKASI FAKTOR PENGHAMBAT PENYEDIAAN HUNIAN PEKERJA INDUSTRI DI KABUPATEN TANGERANG (STUDI KASUS: KAWASAN INDUSTRI & PERGUDANGAN CIKUPAMAS DAN KAWASAN INDUSTRI MILLENIUM) - Ridho Rifky Ariansyah (Universitas Tarumanagara, 2022)
The Central Government's policy that mandates the provision of housing for workers in industrial estates in order to achieve efficiency and effectiveness in industrial estates, as well as in the framework of fulfilling housing for workers in industrial estates is still far from a reality. One of these things happened in industrial areas in the Regency. This condition has occurred for years and in many places, therefore it is interesting to know the causal factors that hinder the realization of housing provision for industrial workers in the Cikupamas Industrial & Warehousing Area and the Millennium Industrial Area, Tangerang Regency, which are the main objectives of this research. To explore these objectives, this study uses a qualitative approach by collecting data through semi-structured interviews, field observations, and processed maps, as well as efforts to validate and validate the data and results that have been collected. Next, the analysis uses content analysis which is obtained through audio recordings, field notes, and documentation in the form of images which will be converted into transcripts for further analysis. The results of this study indicate five factors inhibiting the provision of housing for industrial workers in the Cikupamas Industrial & Warehousing Area and the Millennium Industrial Area, namely the regulatory vacuum at the regional level which should execute the directives of the central government; climate of cooperation between stakeholders that has not been created properly; then limited land in industrial areas; lack of technical coordination between related agencies; and the business orientation tendency of industrial estate managers to override workers' housing needs. What hinders the most is the climate aspect of cooperation between stakeholders (Public Private Partnership), as well as law enforcement carried out by the government/regional government. Keywords: Housing Provision, Industrial Workers, Government Policy, Inhibiting Factors Abstrak Kebijakan Pemerintah Pusat yang mengamanatkan penyediaan hunian bagi pekerja di kawasan industri agar dapat tercapai efisiensi dan efektivitas dalam kawasan industri, serta dalam rangka pemenuhan hunian bagi tenaga kerja di kawasan industri masih jauh dari kenyataan. Hal tersebut salah satunya terjadi di kawasan industri di Kabupaten. Kondisi ini terjadi bertahun-tahun dan banyak tempat, oleh karena itu menarik untuk mengetahui faktor penyebab yang menghambat realisasi penyediaan hunian bagi pekerja industri di Kawasan Industri & Pergudangan Cikupamas dan Kawasan Industri Millenium, Kabupaten Tangerang, yang menjadi tujuan utama penelitian ini. Untuk menggali tujuan tersebut, penelitian ini menggunakan pendekatan kualitatif dengan pengumpulan data melalui wawancara semi struktur, observasi lapangan, dan hasil olahan peta, juga upaya validitas dan keabsahan dari data dan hasil yang telah dikumpulkan. Selnjutnya, analisis menggunakan analisis isi (content analysis) yang didapat melalui rekaman audio, catatan lapangan, dan dokumentasi berupa gambar yang akan diubah menjadi transkrip untuk dianalisis lebih lanjut. Adapun hasil penelitian ini menunjukan lima faktor penghambat penyediaan hunian pekerja industri di Kawasan Industri & Pergudangan Cikupamas dan Kawasan Industri Millenium yakni kekosongan regulasi pada tingkat daerah yang seharusnya mengeksekusi arahan pemerintah pusat; ilkim kerjasama antar stakeholder yang belum tercipta dengan baik; lalu keterbatasan lahan di kawasan industry; minimnya koordinasi teknis antar dinas terkait; dan kecenderungan orientasi bisnis pengelola kawasan industri yang mengesampingkan kebutuhan hunian pekerja. Adapun yang paling menghambat adalah aspek iklim kerjasama antar stakeholder (Public Private Partnership), serta penegakan hukum yang dilakukan oleh pihak pemerintah/pemerintah daerah.